RANCANGAN KUESIONER LIMA ASPEK MINDFULNESS BAHASA INDONESIA - Mutiara, Raden; Suyasa, P. Tommy Y.S. (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
The Facet Mindfulness Questionnaire (FFMQ) is one of the most widely used mindfulness measurement instruments due to the ability of the instrument to assess not only how the individual is at present, but also provides accurate conclusions about the impact of each mindfulness practice that has been practiced before. Unfortunately, the Facet Mindfulness Questionnaire (FFMQ) is not available in Indonesian. The study was conducted to redesign the Five Facet Mindfulness Questionnaire (FFMQ) developed by Baer et al. (2006) in English which consisted of 39 items representing 5 aspects, namely acting with awareness, non-assessing experiences, observing, non-reactivity of inner experiences, and describing in words. The questionnaire redesign in Indonesian version and developed into 40 items consisting of 8 items representing acting with awareness, 9 items representing non-judging of experience, 8 items representing observing, 7 items representing non-reactivity of inner experiences, and 8 items represent describing with words. The questionnaire was arranged in a submitted rating scale format with choices that had been arranged in semantic differential format where response options are presented on a bipolar scale. Kuesioner lima aspek mindfulness atau yang lebih dikenal Facet Mindfulness Questionnaire (FFMQ) adalah salah satu instrumen pengukuran mindfulness yang paling banyak digunakan disebabkan oleh kemampuan instrumen ini menilai bukan hanya bagaimana individu pada saat ini, namun juga memberikan penilaian yang akurat tentang dampak dari setiap praktik mindful yang telah dipraktekkan sebelumnya. Sayangnya saat ini instrumen Facet Mindfulness Questionnaire (FFMQ) belum tersedia dalam bahasa Indonesia. Penelitian dilakukan untuk membuat rancangan kuesioner lima aspek mindfulness atau Five Facet Mindfulness Questionnaire (FFMQ) yang telah dikembangkan oleh Baer et al. (2006) menggunakan bahasa Inggris yang terdiri dari terdiri dari 39 butir yang mewakili 5 aspek yaitu acting with awareness, non-judging of experience, observing, non-reactivity of inner experience, dan describing with words. Kuesioner tersebut yang dirancang kembali dalam bahasa Indonesia dan berkembang menjadi 40 butir yang terdiri dari 8 butir pernyataan mewakili aspek acting with awareness, 9 butir pernyataan mewakili aspek non-judging of experience, 8 butir pernyataan mewakili aspek observing, 7 butir pernyataan mewakili aspek non-reactivity of inner experience dan 8 butir pernyataan mewakili aspek describing with words. Kuesioner disusun dalam format submitted rating scale dengan pilihan respon disusun dalam format semantic differential dimana pilihan respon disajikan dalam skala bipolar.